El trayecto de Santiago Apóstol de Europa al Perú. - Hernández Lefranc, Harold (2006)
The present text travels the trajectory of the speech legitimador of the patron saint Santiago from Spain, from its early presence in the century IX and the process of Spanish reconquest, until the process of American conquest and of the Peru. Santiago restitution symbol of identity and «god» propiciador of the fecundity. Conversion process by the way necessary and recurrent in the history of the religions. Santiago suffered a process in Spain that converts it of irritable fisherman from Galilee, in military degollador enjinetado. The novel elements: «Christian Mohammed» and «Cástor dioscúrico». In the Peru in the dependent sectors was never successful some «Santiago mataindios». The tramped character and murdered under the paws of the steed it was never Indian in the speech of subordinate sectors. Also, these always identified Santiago with Illapa or similar. The text stops at this time of reinterpretación.